Hepatic osteodystrophy: molecular mechanisms proposed to favor its development - Ehnert, Sabrina; Aspera-Werz, Romina H.; Ruoß, Marc; Dooley, Steven; Hengstler, Jan G.; Nadalin, Silvio; Relja, Borna; Badke, Andreas; Nussler, Andreas K. (International journal of molecular sciences, 2019)
Almost all patients with chronic liver diseases (CLD) show altered bone metabolism. Depending on the etiology, this manifests in a severe osteoporosis in up to 75% of the affected patients. Due to high prevalence, the generic term hepatic osteodystrophy (HOD) evolved, describing altered bone metabolism, decreased bone mineral density, and deterioration of bone structure in patients with CLD. Once developed, HOD is difficult to treat and increases the risk of fragility fractures. Existing fractures affect the quality of life and, more importantly, long-term prognosis of these patients, which presents with increased mortality. Thus, special care is required to support the healing process. However, for early diagnosis (reduce fracture risk) and development of adequate treatment strategies (support healing of existing fractures), it is essential to understand the underlying mechanisms that link disturbed liver function with this bone phenotype. In the present review, we summarize proposed molecular mechanisms favoring the development of HOD and compromising the healing of associated fractures, including alterations in vitamin D metabolism and action, disbalances in transforming growth factor beta (TGF-β) and bone morphogenetic protein (BMP) signaling with histone deacetylases (HDACs) as secondary regulators, as well as alterations in the receptor activator of nuclear factor kappa B ligand (RANKL)–osteoprotegerin (OPG) system mediated by sclerostin. Based on these mechanisms, we give an overview on the limitations of early diagnosis of HOD with established serum markers.